ENVIRONMENTAL SANITATION IN MAINTAINING THE QUALITY OF LIFE IN THE MANGROVE BEACH AREA - Wasiyem, Wasiyem; Fadil Rangkuti, Ahmad; Suhailah, Nadiyah; Arni, Amira; Melati, Septira; Dwi Fahira, Annisa (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Mangrove forest is one of the plant communities that live in coastal areas. One of the causes of inhibiting the proliferation of mangrove forests is garbage disposal, the impact of garbage pollution will affect marine biota. Many tourists throw garbage in the mangrove forest area and this garbage can damage the growth of mangrove trees. The purpose of this study was to determine environmental sanitation in coastal areas and mangrove forests. This type of research is to use a descriptive qualitative research design in the form of written or spoken words from people and observed behavior. The results of the study show that the environment around the mangrove forest can be categorized as fulfilling the requirements. However, there are still several problems, such as the management of waste that is directly burned individually and not transported by the government. The availability of clean water and mangrove trees are put to good use.